O ARROZ DE VENEZA E OS TRABALHADORES DE GUINÉ: A lavoura de exportação do Estado do Maranhão e Piauí (1770-1800) - Junior, Reinaldo dos Santos Barroso (Outros Tempos: Pesquisa em Foco - História, 2011)
The territory of Maranhão, during the colonial period, was a major producer andexporter of rice, especially in the last quarter of the eighteenth century. The productionof rice was made possible by Africans of the Upper Guinea, West African territory. The fame ofthese Africans as skilled producers of rice Oryza glaberrima (African rice) extendedfrom across the Atlantic - this was apparently specific knowledge of the cultivation of this cereal thatexcited the interest of farmers and government officials in different localities. Maranhãoimported from port of Bissau, Cacheu and nearby, a lot of these Africans by virtue of this apparentqualification on rice production. The large-scale production of rice in the state ofMaranhao and Piaui, in the second half of the eighteenth century, symbolizes the qualificationof guineensis and the importance of Africans to export project implemented in the colonies.